2023
DOI: 10.1111/jhn.13126
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phone and video counselling given to participants living with obesity on weight loss and quality of life during the COVID‐19 pandemic: a randomised controlled trial

Abstract: Background Although remote dietary counselling practices have increased in the COVID‐19 pandemic, it is not known which method is more effective. This study aimed to determine the effect of diet counselling by phone or video on weight loss and to compare it with the traditional follow‐up method. Methods Forty‐six participants living with obesity were randomised into the phone counselling ( n = 15), video counselling ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Beyond engagement, research suggests that delivering weight‐loss programs in‐person or remotely may have no significant effect on weight loss or retention rates. 20 Yucel and Yucel, 22 however, found that both phone‐and video‐counseling were more effective at promoting weight loss than traditional in‐person group counseling sessions. Taken together, these findings suggest that further evidence is needed to understand the effectiveness of remotely delivered interventions in fostering sustained engagement and weight‐loss maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond engagement, research suggests that delivering weight‐loss programs in‐person or remotely may have no significant effect on weight loss or retention rates. 20 Yucel and Yucel, 22 however, found that both phone‐and video‐counseling were more effective at promoting weight loss than traditional in‐person group counseling sessions. Taken together, these findings suggest that further evidence is needed to understand the effectiveness of remotely delivered interventions in fostering sustained engagement and weight‐loss maintenance.…”
Section: Introductionmentioning
confidence: 99%